2012
DOI: 10.3892/ijmm.2012.1072
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 siRNA suppresses the inflammatory response induced by oxLDL through inhibition of NF-κB activation in THP-1-derived macrophages

Abstract: Proprotein convertase subtilisin/kexin 9 (PCSK9), a member of the protein-converting enzyme family, is highly expressed in adult hepatocytes and small intestinal enterocytes. To our knowledge, in this study, we demonstrate for the first time that PCSK9 is upregulated in a dose-dependent manner via oxidized low-density lipoprotein (oxLDL) stimulation in THP-1-derived macrophages. PCSK9 small interfering RNA (siRNA) suppresses the oxLDL-induced inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
139
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 35 publications
0
139
0
Order By: Relevance
“…The positive correlation between the PLT count and LDL-C level and multiple metabolic factors reported in population studies suggests a potential link between the PLT count and dyslipidemia 1,2) . Secondly, experimental studies have shown that lipopolysaccharide-induced inflammation stimulates the expression of PCSK9, whereas knockdown of PCSK9 mediated by small-interfering RNA (siRNA) attenuates the ox-LDL-induced expression of proinflammatory genes 20,21) . Clinically, we found that the plasma PCSK9 level seems to be independently associated with traditional markers of chronic low-grade inflammation 7) .…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the PLT count and LDL-C level and multiple metabolic factors reported in population studies suggests a potential link between the PLT count and dyslipidemia 1,2) . Secondly, experimental studies have shown that lipopolysaccharide-induced inflammation stimulates the expression of PCSK9, whereas knockdown of PCSK9 mediated by small-interfering RNA (siRNA) attenuates the ox-LDL-induced expression of proinflammatory genes 20,21) . Clinically, we found that the plasma PCSK9 level seems to be independently associated with traditional markers of chronic low-grade inflammation 7) .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) is a transcription factor that has crucial roles in inflammation, immunity, cell proliferation and apoptosis (4)(5)(6). Activation of NF-κB is controlled by the inhibitor of κB (I-κB), which retains NF-κB in the cytoplasm (7).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data show that PCSK9 is markedly induced by diverse inflammatory stimuli, such as lipopolysaccharides, zymosan, and turpentine 33) , resulting in a significant increase in LDL-C levels. Importantly, oxidized LDL (oxLDL), a major proinflammatory factor in the development of atherosclerosis, also increases PCSK9 expression by altering the secretion of inflammatory chemokines, such as interleukin-1 (IL-1 ), IL-6, and tumor necrosis factor-, in THP-1-derived macrophages in a dose-dependent manner 34) . Furthermore, siRNA-mediated knockdown of PCSK9 suppresses oxLDL-induced proinflammatory chemokine synthesis and secretion by inhibiting nuclear factor kappa B alpha degradation and nuclear factor kappa B translocation, which have an anti-inflammatory role in macrophages 34) .…”
Section: Pcsk9 and Inflammationmentioning
confidence: 99%
“…Importantly, oxidized LDL (oxLDL), a major proinflammatory factor in the development of atherosclerosis, also increases PCSK9 expression by altering the secretion of inflammatory chemokines, such as interleukin-1 (IL-1 ), IL-6, and tumor necrosis factor-, in THP-1-derived macrophages in a dose-dependent manner 34) . Furthermore, siRNA-mediated knockdown of PCSK9 suppresses oxLDL-induced proinflammatory chemokine synthesis and secretion by inhibiting nuclear factor kappa B alpha degradation and nuclear factor kappa B translocation, which have an anti-inflammatory role in macrophages 34) . In our clinical study, we reportedthat plasma PCSK9 levels are associated with traditional markers of chronic low-grade inflammation, which are known CAD risk factors, such as circulating white blood cell count and platelet count 13,35) .…”
Section: Pcsk9 and Inflammationmentioning
confidence: 99%